137 Sustained freedom from disease activity over 3 years in an Irish Cohort with highly active Multiple Sclerosis. Issue 3 (9th February 2012) - Kelly, S; Kinsella, K; Duggan, M; Hutchinson, M; Tubridy, N; McGuigan, C
Abstract : Introduction: The efficacy of natalizumab in highly active RRMS is well established. Recent studies have focused on the concept of disease freedom with Natalizumab. Aim: The aim of this study was to examine a cohort of patients who received up to 3 years of natalizumab to identify those who became free of identifiable disease activity. Methods: We performed a retrospective review of all patients who completed at least one full year of treatment from August 2006 until 1 May 2011. Baseline annualised relapse rates (ARR) and EDSS prior to commencing therapy were established. Patients who had no clinical relapses, progression in expanded disability status scale (EDSS) or MRI activity (absence of new T2 and gadolinium-enhancing (Gad +ve) lesions on annual MRI) were deemed disease-free. Results: Of 111 patients follow-up data were available for 1 year on 71 patients, 2 years on 50 and 3 years on 26 patients. The baseline ARR was1.8, mean EDSS 3.0. 39/71 (55%) patients were free from disease activity at 1 year, at 1 years 18/50 (36%) and after 3 years 8/26 (31%). Conclusion: A significant proportion of our patients treated with natalizumab obtained sustained freedom from disease activity even after 3 years of follow-up.